Man without a face the autobiography at communism's greatest spymaster - Wolf, Markus 1923-2006; McElvoy, Anne 1965- (Public Affairs, 1999)
The former head of East Germany's foreign intelligence department describes his career in espionage and life in the post-Cold War world.